On the development of flow-ecology relationships for streams in coastal watersheds of southern California - Eberhart, Sarah R., author; Bledsoe, Brian P., advisor; Poff, N. LeRoy, committee member; Stein, Eric D., committee member (Colorado State University. Libraries, 2014)
Linking hydrologic alteration to the biotic responses of streams is essential for understanding and managing the effects of land use changes and other human influences on aquatic ecosystems. This study develops flow-ecology relationships for wadeable streams in coastal watersheds of southern California to understand the ecological effects of urbanization and other sources of hydromodification. Streams in this region are predominately flashy, seasonally intermittent, and fine grained; hence, the inherently harsh disturbance regime is a major determinant of biotic composition. I match biological and geomorphic data with proximate U. S. Geological Survey streamflow gages to examine flow-ecology relationships between benthic macroinvertebrates and the hydrologic and hydraulic regimes of 32 biomonitoring sites spanning a gradient of watershed urbanization. Associations between landscape, streamflow, and biotic metrics indicate that flow permanence and urbanization are overarching and interacting influences on benthic macroinvertebrate assemblages in this region. In particular, flow intermittency and flashiness are significant predictors of both taxonomic and traits-based measures of biotic composition. Urban land cover and road density are significantly correlated with higher flow flashiness and decreasing measures of biotic integrity. Hydraulic metrics describing streambed mobility are strongly positively associated with measures of biotic integrity as a result of high intercorrelation with flow permanence. Thus, it appears that benthic macroinvertebrate assemblages are fundamentally influenced by flow intermittency and urban-induced flashiness in this region. Use of daily discharge data analyzed 3 yrs prior to biological sampling events appears to result in little to no loss of resolution in flow-ecology relationships compared to sub-daily (15-min) and long-term (decadal) flow records. Results also underscore the utility of traits-based analyses and stratification of sites by flow permanence and dominant substrate in revealing mechanistic relationships between flow and biotic metrics. By using gaged sites to identify the flow metrics best describe biological variation, this study provides insight into which elements of the flow regime are most important to model accurately in future efforts to develop a regional hydrologic foundation that will allow the inclusion of ungaged biomonitoring sites in refining flow-ecology relationships.